Pengaruh Penggunaan Media Pembelajaran Visual Terhadap Minat Belajar Siswa Pendidikan Agama Kristen Budi Pekerti Kelas VIII SMP N 2 Doloksanggul Tahun Ajaran 2022/2023 - Remenci Sihite; Malani Simanungkalit; Maria Widiastuti (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study was to determine the effect of the use of visual learning media on students' interest in learning Christian Religious Education Budi Pekerti class VIII SMP N 2 Doloksanggul School Year 2022/2023. The research method used is descriptive quantitative research method. The population was all VIII grade students of SMP N 2 Doloksanggul in the 2022/2023 academic year totaling 135 people and a research sample of 39 people was determined using the Simple Random Sampling technique. Data were collected using a positive closed questionnaire as many as 30 items, namely 15 items for variable X and 15 items for variable Y. The results of data analysis showed that there was an influence of the use of visual learning media on the interest in learning Christian Religious Education students of class VIII SMP N 2 Doloksanggul in the 2022/2023 academic year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.536 > rtable (a=0.05, n=39) = 0.316. b) significant relationship test obtained tcount = 3.860 > ttable (a=0.05, dk=n-2=37) = 2.021. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂ = "25", "56"+0.48X. b) Regression determination coefficient test (r2) = 28.7%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (a=0.05, dk numerator k = 17, dk denominator = n-2 = 39-2 = 37), namely 14.10> 1.51. Thus Ha, namely that there is an effect of the use of visual learning media on student interest in learning Christian Religious Education Budi Pekerti class VIII SMP N 2 Doloksanggul School Year 2022/2023, is accepted and H0 is rejected.